Gene-edited pigs: a translational model for human food allergy against alpha-Gal and anaphylaxis - Wang, Ying; Hils, Miriam; Fischer, Andrea; Wölbing, Florian; Biedermann, Tilo; Schnieke, Angelika; Fischer, Konrad (Frontiers in Immunology, 2024)
The prevalence of food allergy is rising and are estimated to approach 10%. Red meat allergy is the first known food allergy elicited by immunoglobulin E (IgE) antibodies recognizing a carbohydrate. Due to the loss of function of the alpha-1,3-galactosyltransferase (GGTA1) gene in humans, the disaccharide galactose-α-1,3-galactose (α-Gal) cannot be synthesized and therefore became immunogenic. IgE sensitization is elicited through the skin by repetitive tick bites transmitting α-Gal. The underlying mechanisms regarding innate and adaptive immune cell activation, including the B cell isotype switch to IgE, are poorly understood, requiring further research as well as physiologically relevant animal models. Here we describe a new animal model of red meat allergy using percutaneous α-Gal sensitization of gene edited GGTA1 deficient pigs. Total and α-Gal specific IgG, IgG1, IgG2, IgG4 and IgE levels were tracked. Further key factors associated with allergic skin inflammation, type 2 immunity and allergy development were measured in PBMCs and skin samples. Significant increases in α-Gal specific IgG1 and IgE levels indicated successful sensitization to the allergen α-Gal. Intracutaneous sensitizations with α-Gal recruited lymphocytes to the skin, including elevated numbers of T helper 2 (Th2) cells. Finally, α-Gal sensitized pigs not only recognized α-Gal as non-self-antigen following α-Gal exposure through the skin but also developed anaphylaxis upon antigen challenge. Based on the similarities between the porcine and human skin, this new large animal model for α-Gal allergy should help to unveil the consecutive steps of cutaneous sensitization and aid the development of prophylactic and treatment interventions.